Assessment of right ventricular systolic function in heart transplant patients: Correlation between echocardiography and cardiac magnetic resonance imaging. Investigation of the accuracy and reliability of echocardiography. Issue 10 (28th August 2017) - Simsek, Evrim; Nalbantgil, Sanem; Ceylan, Naim; Zoghi, Mehdi; Kemal, Hatice Soner; Engin, Cagatay; Yagdi, Tahir; Ozbaran, Mustafa
Abstract : Background: Right ventricular (RV) function has great impact on the survival of heart transplantation recipients; therefore, careful evaluation is of high clinical importance. However, there is no standard conventional echocardiographic parameter to assess RV systolic function. Herein, we evaluated the correlation between echocardiographic parameters of RV systolic function and ejection fraction assessed by cardiac magnetic resonance imaging (MRI RVEF) in heart transplantation recipients. Method and Results: Forty‐three patients with at least 6‐month heart transplantation history were included in this study. Each patient had conventional echocardiography and cardiac MRI evaluation, followed by endomyocardial biopsy and right heart catheterization, which were performed in six hours. Echocardiographic parameters of RV systolic function, RV fractional area change (RV FAC), tricuspid annular plane systolic excursion (TAPSE), RV myocardial performance index, and RV global longitudinal strain, were compared with MRI RVEF ( P values were <0.001, <0.3, <0.9, and <0.4, respectively). RV FAC was the only parameter to strongly correlate with MRI RVEF ( r =0.747, P <0.001); and RV FAC 48.5% value had 90.5% sensitivity and 90.5% specificity to predict the pathologic reference value of MRI RVEF ≤50% (AUC:0.96; 95% CI, 0.908–1.013). Conclusion: To our knowledge, this is the first prospective study to evaluate the correlation between the echocardiographic parameters for RV systolic function and MRI RVEF in heart transplantation recipients. RV FAC is the only parameter to correlate well with MRI RVEF, and its routine use in the follow‐up of heart transplantation recipients should be considered.